Giorgio Chittolini, ‘historian’ and ‘teacher’: a personal remembrance (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The recent death of Giorgio Chittolini, one of Italy’s leading medievalists, provides an opportunity for a personal remembrance and a brief reflection on his scholarly personality, also in light of his latest collection of essays on ecclesiastical institutions.
Keywords: Giorgio Chittolini; Middle Ages; Historiography; Ecclesiastical Institutions